183k views
5 votes
Solve for x. x+2/3=−1/6

User Apple
by
5.1k points

2 Answers

4 votes

Hello! :)

First, Simplify both sides of the equation

x + 2/3= -1/6

Next, Subtract 2/3 from both sides

x + 2/3 - 2/3 = -1/6 - 2/3

x= -5/6 (ANSWER)

Hope this helped you!

THEDIPER

User Man Person
by
4.5k points
5 votes

Answer:

-5/6

Explanation:


x+(2)/(3) = (-1)/(6)

By transposing 2/3 towards the RHS we get,


x=(-1)/(6) -(2)/(3)


x=-(1)/(6) -(2X2)/(3X2) =-(1)/(6) -(4)/(6) =(-5)/(6)

User Oleksandr Diudiun
by
5.5k points